2013
DOI: 10.1371/journal.pone.0073118
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Delivery of Plasma and Platelet Growth Factors Using PRGF-Endoret System Enhances Neurogenesis in a Mouse Model of Alzheimer’s Disease

Abstract: Neurodegeneration together with a reduction in neurogenesis are cardinal features of Alzheimer’s disease (AD) induced by a combination of toxic amyloid-β peptide (Aβ) and a loss of trophic factor support. Amelioration of these was assessed with diverse neurotrophins in experimental therapeutic approaches. The aim of this study was to investigate whether intranasal delivery of plasma rich in growth factors (PRGF-Endoret), an autologous pool of morphogens and proteins, could enhance hippocampal neurogenesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 61 publications
4
52
3
2
Order By: Relevance
“…2 and 4). Similar anti-apoptotic effects of PRGF technology have been previously reported on a mouse model of Alzheimer's disease [27,28].…”
Section: Discussionsupporting
confidence: 82%
“…2 and 4). Similar anti-apoptotic effects of PRGF technology have been previously reported on a mouse model of Alzheimer's disease [27,28].…”
Section: Discussionsupporting
confidence: 82%
“…In addition, we demonstrated that PRGF-Endoret appears to possess an inherent NF-kB-mediated antiinflammatory function in this AD model [27]. Most interestingly, PRGF-Endoret acts as neurotrophic factor promoting neuronal survival under amyloid beta (A) exposure [28].…”
Section: Introductionmentioning
confidence: 79%
“…One previous study showed that PRGF-Endoret enhances hippocampal neurogenesis after intranasal application in a mouse model of AD [28], and very recently, PRGFEndoret proved to be neuroprotective in transgenic APP/PS1 mice, with multifunctional and complementary effects that result in the reversal of the broad range of cognitive deficits in AD [27]. PRGF-Endoret constitutes a biological system that provides a complex pool of growth factors that may stimulate and accelerate tissue regeneration [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is indicated that hippocampal neurogenesis may increase during the development of AD [57]. It is suggested that neurogenesis in APP/PS1 mice might be a compensatory effect for pathologic changes, and AD brain tissue may exist some toxic factors on neurogenesis [58]. Therefore, it is necessary to give some appropriate stimulus for the neurogenesis of neurons.…”
Section: Neurogenesismentioning
confidence: 99%